PENERAPAN METODE SOLFEGIO PADA PEMBELAJARAN BERMAIN MUSIK IRINGAN TARI DI SMA NEGERI 1 PADANG - Handika Rizki Ramadhan; Erfan Erfan; Irdhan Epria Dharma Putra (SENDRATASIK UNP, 2018)
Abstract This study aims to describe the application of solfeggio method as the students success rate support in playing dance accompaniment music in art and cultural subject as well as the relevance of learning to play the music of dance accompaniment on the students.  This research was categorized into qualitative research using descriptive analysis approach. The object of research was 11th-grade students of SMA Negeri 1 Padang. Techniques of data collection used in this study include observation, interviews, literature study and documentation. The results show that the application of solfeggio method on Dance accompaniment Music Learning towards the 11th-grade students of SMA Negeri 1 Padang has a high impact of success rate. Applications of solfeggio method led students to have ability development and facilitated the students in making dance accompaniment music. From the 30 students in the classroom, 18 students succeeded in learning well and got values above the average learning outcomes standard in cultural arts learning. 7 students got standard grade scores, and 5 others were below the standard score. It shows that 83.3% of the total students have the high skill level. Keyword: Solfegio, Method and music accompaniment dance.